An Uncommon Cause of Intraoperative Hypotension: Delayed Red Man Syndrome - Nagmoti, Shilpa V.; Prathapadas, Unnikrishnan; Hrishi, Ajay P. (Journal of Neuroanaesthesiology and Critical Care, 2019)
Intraoperative hypotension is commonly encountered under anesthesia. Varied causation of intraoperative hypotension can often delay the recognition of its cause. Vancomycin, a bactericidal antibiotic and often used in neurosurgical setting, is known to cause “red man syndrome.” Prompt recognition of the etiology for intraoperative hypotension could be challenging in intraoperative setting. We present a case of intraoperative hypotension in a patient undergoing endoscopic skull base surgery, which was caused by a delayed red man syndrome. Delayed red man syndrome is a rare clinical entity and must be borne in mind while evaluating a case of intraoperative hypotension in patients who are on vancomycin therapy.
Keywords: vancomycin; hypotension; neurosurgery